Spread of Respiratory Pathogens During the COVID-19 Pandemic Among Children in the Northeast of Italy - Cason, Carolina; Zamagni, Giulia; Cozzi, Giorgio; Tonegutto, Davide; Ronfani, Luca; Oretti, Chiara; De Manzini, Andrea; Barbi, Egidio; Comar, Manola; Amaddeo, Alessandro (Frontiers in Microbiology, 2022)
The social distancing measures adopted during COVID-19 pandemic led to a profound change in the behavioral habits of the population. This study analyzes the impact of restriction measures on the shaping of the epidemiology of common winter respiratory pathogens in the pediatric population of the North-East of Italy. From September 2020 to March 2021, a total of 1227 nasopharyngeal swabs from symptomatic pediatric patients were tested for the presence of SARS-CoV-2, influenza A and B, adenovirus, other coronaviruses, parainfluenza virus 1–4, enterovirus, bocavirus, metapneumovirus, respiratory syncytial virus, rhinovirus, Bordetella pertussis, Bordetella parapertussis and Mycoplasma pneumoniae. To relate virus positivity with the clinic characteristics of the subjects enrolled, bivariate logistic models were estimated. SARS-CoV-2 was detected in 5.2% of the children, fever resulted as risk factor for infection (OR=2.03, p=0.03). Rhinovirus was detected in the 40.7% of the subjects, with cough and rhinitis as risk factors (respectively OR=2.17, p<0.001 and OR=2.86, p<0.001). Other coronaviruses were found in 10.8% of children, and were associated to pharyngodynia (OR=2.89, p<0.001). Adenovirus, observed in 11.6% of subjects, showed to have fever as risk factor (OR=5.66, p<0.001). Bocavirus was detected in 3.2% of children. In conclusion, our results showed that social isolation measures had an impact on the circulation of RSV and influenza, although children under the age of two were most affected by the other respiratory infections. Therefore, this study highlights the need for continuing surveillance for a delayed spread of RSV and other respiratory pathogens.